ITB AAS Indonesia Informatics Study Program Value Information System - Rozaq Rais, Nendy Akbar (Institut Teknologi Bisnis AAS Indonesia, 2023)
The Grade Management Information System (SIPAN) is a web-based grade information system in the ITB AAS Indonesia informatics study program which is used to support the activities of lecturers in conveying the grades of the courses taught, administrative officers in terms of grade recapitulation, student grade information which is private, and supports activities of the study program coordinator in monitoring the development of academic activities in terms of grades. The aim and objective of developing SIPAN is to assist higher education institutions in managing student grades. With web-based software, lecturers can submit student grades at any time within a predetermined time period and have an internet connection. Likewise with students, they can see their own grades anytime, anywhere, as long as they have an internet connection. The study program coordinator can monitor the extent to which lecturers at their home base match their grades. The expected final result will be the realization of a well-integrated information technology-based student grades management process, neat record keeping, and integration with the Attendance Information System.